A method of estimating aborted transaction in the database concurrency control system - Mat Deris, Mustafa; Mamat, Ali (Faculty of Computer Science and Information Technology, University of Malaya, 1997)
Transactions may be aborted when they are unable to obtain a lock on a required data item. Estimating the proportion of transaction that aborts is one of the key issues in modelling a system which affect the performance measures of interest such as average response time and the throughput capacity of the system. This paper shows a method of estimating aborted transaction and performs a comparative study with other method given by Mitrani et al.